High-absorbability hydrogel as well as preparation method and application thereof
The preparation of hydrogels by cross-linking of recombinant collagen or peptide compounds with sodium carboxymethylcellulose solves the problem of reducing intake after expansion in the gastrointestinal tract, achieving high water absorption and energy delivery capabilities, ensuring the safety of nutrient intake.
Patent Information
- Application Number
- CN202510090801.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Existing hydrogels reduce human food intake after expanding in the gastrointestinal tract. Long-term use may lead to malnutrition, and their water absorption rate and mechanical strength are insufficient.
Recombinant collagen or peptide compounds are used as crosslinking agents to react with sodium carboxymethylcellulose to form a loose polymer network structure, improve the water absorption rate of the hydrogel and provide energy.
It improves the swelling rate and energy-providing capacity of the hydrogel, ensuring that it does not affect the body's nutritional intake while providing a feeling of fullness.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogel preparation, and in particular relates to a highly absorbent hydrogel and a preparation method and application thereof. Background Art
[0002] Hydrogel is a hydrophilic three-dimensional network structure gel that can absorb water, causing it to swell to multiple times its initial volume. Hydrogels are usually made of natural or synthetic polymers that are cross-linked physically (non-covalently) or chemically (covalently) (Reference 1: JIANG Q, ZHOU W, WANG J, et al. Hypromellose succinate-crosslinked chitosan hydrogel films for potential wound dressing [J]. International Journal of Biological Macromolecules, 2016, 91: 85-91.). Highly absorbent hydrogels can absorb 10 times their own weight, and some can even reach more than 1,000 times, with super strong absorption properties.
[0003] Specifically, hydrogels, as a type of macromolecular polymer, can be produced by physical or chemical crosslinking. Physical crosslinking is usually formed by the association of molecules through hydrogen bonds, interionic forces, crystallization, hydrophobic interactions, etc. This intermolecular interaction force is generally reversible, so the stability and mechanical strength of the hydrogel are poor. Chemical crosslinking is formed by the connection of polymer molecular chains through covalent bonds. Compared with intermolecular forces, chemical bonds are more solid, thus giving the hydrogel more stable and better strength properties. The chain length of the crosslinking agent used in the chemical crosslinking method will affect the water absorption rate and mechanical strength. When a short crosslinking agent such as a dicarboxylic acid is used, because of its short length, after crosslinking with a polysaccharide chain at one end, the other end can only react with the same polysaccharide chain or another adjacent polysaccharide chain, which will lead to the formation of intramolecular crosslinking or a tightly connected intermolecular crosslinking network structure. This dense structure is not conducive to the retention of water molecules and reduces the swelling degree of the product. Therefore, in the preparation technology of hydrogels, the chemical crosslinking method can prepare a stable and rigid polymer network structure compared to physical crosslinking. The chain length of the crosslinking agent affects the water absorption capacity and strength of the hydrogel. The existing technology usually uses a short chain length crosslinking agent to produce a denser molecular structure, but it also brings about the problem of low mechanical strength and low water absorption rate of the hydrogel.
[0004] Highly absorbent hydrogels are often used as gastrointestinal fillers in the medical field. After taking them, they can absorb body fluids and swell, occupying the volume of the gastrointestinal tract and producing a feeling of fullness. However, most of the hydrogels currently used as gastric fillers on the market are cellulose polysaccharide products, which cannot be absorbed by the human body. After swelling in the gastrointestinal tract, they will reduce the body's food intake. Long-term use may cause malnutrition.
[0005] Therefore, it is necessary to develop a new hydrogel product that can both give a sense of fullness and provide energy to the body. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a highly absorbent hydrogel and a preparation method and application thereof. Recombinant collagen / peptide compounds and sodium carboxymethyl cellulose are used as raw materials, and a chemical cross-linking reaction occurs at a certain temperature to form a loose polymer network structure, so that the obtained hydrogel has a higher swelling rate, which can provide energy to the human body while providing a sense of fullness.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention:
[0009] A method for preparing a highly absorbent hydrogel, using recombinant collagen or a peptide compound as a crosslinking agent and reacting with sodium carboxymethyl cellulose to prepare the hydrogel, comprising the following steps:
[0010] dissolving the cross-linking agent in water to obtain solution I;
[0011] Adding sodium carboxymethyl cellulose to the solution I to obtain a solution II;
[0012] The solution II is dried and crushed into particles, which are then heated to undergo esterification and cross-linking reaction to obtain the highly absorbent hydrogel.
[0013] Recombinant collagen is the earliest discovered and most abundant type of extracellular matrix protein, which is widely found in the skin, muscles, bones and internal organs of humans and animals. Collagen is widely used in food, cosmetics, nutritional supplements and other fields because of its excellent physical and chemical properties, biological efficacy, biocompatibility, biodegradability and other characteristics. According to the source, collagen is roughly divided into animal collagen and recombinant collagen. Due to the potential pathogenic risks and immunogenicity of animal collagen, with the development of synthetic biology, the market share of recombinant collagen continues to increase. At the same time, the hydrolysis product of protein, oligopeptides (the number of amino acids on the peptide chain is less than 10) or polypeptides (the number of amino acids on the peptide chain is between 10 and 50) can also be used as long-chain cross-linking agents to prepare highly absorbent hydrogels.
[0014] The present invention uses recombinant collagen or peptide compounds with long chains as crosslinking agents. Since such crosslinking agents have longer chains, when the crosslinking agents are crosslinked with the polysaccharide chains in sodium carboxymethyl cellulose, the other end has a larger range of movement and is more likely to be crosslinked with more polysaccharide chains, thereby increasing the crosslinking between molecules. At the same time, the crosslinking network structure is looser, and the pores are enlarged to accommodate more water molecules, thereby increasing the water absorption rate.
[0015] Furthermore, the mass concentration of the cross-linking agent in the solution I is 1-6%.
[0016] Furthermore, the mass concentration of sodium carboxymethyl cellulose in the solution II is 6-10%.
[0017] Furthermore, the recombinant collagen is selected from one or more of type I, type II, type III, type V, type IV and type XVII.
[0018] Furthermore, the peptide compound is selected from one or more of oligopeptides or polypeptides.
[0019] Furthermore, the drying temperature is 40-60° C., and the drying time is 24-120 h, preferably 48-72 h.
[0020] Furthermore, the temperature of the esterification cross-linking reaction is 100-150° C., and the time is 1-24 hours, preferably 3-8 hours.
[0021] Furthermore, the particle size of the particles is 0.05-5 mm, preferably 0.1-1 mm.
[0022] The second technical solution of the present invention:
[0023] A highly absorbent hydrogel is prepared according to the above preparation method.
[0024] The third technical solution of the present invention:
[0025] The highly absorbent hydrogel is used in preparing medicine for treating overweight or obesity.
[0026] The fourth technical solution of the present invention:
[0027] The highly absorbent hydrogel is used in preparing a medicine for treating sleep apnea.
[0028] The fifth technical solution of the present invention:
[0029] The highly absorbent hydrogel is used in preparing medicine for treating diabetes.
[0030] Compared with the prior art, the present invention has the following advantages and technical effects:
[0031] (1) The present invention uses recombinant collagen or peptide compounds as crosslinking agents. The main chain ends and side chains of the crosslinking agents contain abundant carboxyl and amino groups, which can react with the polysaccharide chains in sodium carboxymethyl cellulose to generate a loose polymer network and improve the water absorption rate. On the other hand, the addition of recombinant collagen or peptide compounds can also be used as an energy substance to provide energy for the body and prevent malnutrition caused by long-term reduction of food intake.
[0032] (2) The present invention proposes for the first time to prepare a hydrogel by cross-linking recombinant collagen / peptide compounds with sodium carboxymethyl cellulose. The preparation method is simple, safe and non-toxic. After consuming the hydrogel of the present invention, the patient feels full and can provide energy to the body, thereby broadening the selection of gastrointestinal fillers. DETAILED DESCRIPTION
[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0034] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0035] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0036] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0037] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0038] The embodiment of the present invention provides a method for preparing a highly absorbent hydrogel, which is prepared by cross-linking reaction between recombinant collagen or a peptide compound as a cross-linking agent and sodium carboxymethyl cellulose, and specifically comprises the following steps:
[0039] dissolving the cross-linking agent in water to obtain solution I;
[0040] Adding sodium carboxymethyl cellulose to the solution I to obtain a solution II;
[0041] The solution II is dried and crushed into particles, which are then heated to undergo esterification and cross-linking reaction to obtain the highly absorbent hydrogel.
[0042] In a preferred embodiment of the present invention, the mass concentration of the cross-linking agent in the solution I is 1-6%, preferably 5%.
[0043] In a preferred embodiment of the present invention, the mass concentration of sodium carboxymethyl cellulose in the solution II is 6-10%, preferably 6%.
[0044] In a preferred embodiment of the present invention, the recombinant collagen is selected from one or more of type I, type II, type III, type V, type IV and type XVII, preferably type III recombinant collagen.
[0045] Recombinant collagen is divided into different types according to its molecular structure, tissue distribution, physiological function and gene coding, including type I, type II, type III, type V, type IV and type XVII. The following are the main differences between these types:
[0046] Type I collagen: This is the most common type of collagen and is found primarily in skin, bones, tendons, and other connective tissues, providing structural support and strength.
[0047] Type II collagen: Mainly found in cartilage tissue, it is a key component in maintaining joint health and elasticity.
[0048] Type III collagen: Found in skin, blood vessels, muscles, and internal organs, it helps maintain the elasticity and stability of these tissues.
[0049] Type IV collagen: Mainly found in the basement membrane, it plays an important role in supporting and separating tissue cells.
[0050] Type V collagen: Usually present together with type I and type II collagen, affecting the assembly of the extracellular matrix and cell adhesion.
[0051] Type XVII collagen: mainly coexists with type I and type II collagen, and is involved in regulating the diameter of collagen fibers and the integrity of tissue structure.
[0052] In a preferred embodiment of the present invention, the peptide compound is selected from one or more of oligopeptides or polypeptides.
[0053] During the hydrolysis process of protein, the triple helix structure is destroyed and it is broken down into polypeptides or oligopeptides with relatively small molecular weight. Oligopeptides usually refer to peptides composed of 2 to 10 amino acid residues with a small molecular weight, usually less than 1000 Daltons. Polypeptides refer to peptides composed of more than 10 but less than 50 amino acid residues, with a molecular weight between 1000 and 10000 Daltons.
[0054] In a preferred embodiment of the present invention, the drying temperature is 40-60° C., and the drying time is 24-120 h, preferably 48-72 h.
[0055] In a preferred embodiment of the present invention, the temperature of the esterification cross-linking reaction is 100-150° C., and the time is 1-24 hours, preferably 3-8 hours.
[0056] In a preferred embodiment of the present invention, the particle size of the particles is 0.05-5 mm, preferably 0.1-1 mm.
[0057] The embodiment of the present invention also provides a highly absorbent hydrogel, which is prepared according to the above preparation method.
[0058] The room temperature in the embodiments of the present invention refers to "20-25°C".
[0059] The recombinant collagen used in the examples of the present invention is type III recombinant collagen, which was purchased from Jiangsu Chuangjian Medical Technology Co., Ltd., and the sodium carboxymethyl cellulose used was purchased from Anhui Shanhe Pharmaceutical Excipients Co., Ltd. The oligopeptides and polypeptides used were purchased from Shanghai Hongpeptide Biotechnology Co., Ltd., wherein the polypeptide sequence is DDDDKAPFFDDDD, and the oligopeptide sequence is DDDDKAPFF.
[0060] The technical solution of the present invention is further illustrated by the following embodiments.
[0061] Example 1
[0062] (1) dissolving type III recombinant collagen in water at room temperature to obtain solution I with a mass concentration of 5%;
[0063] (2) adding sodium carboxymethyl cellulose to solution I obtained in step (1), stirring and mixing for 5 hours to obtain solution II, wherein the mass concentration of sodium carboxymethyl cellulose in solution II is 6%;
[0064] (3) Pour solution II from step (2) into a stainless steel plate and dry in a 50° C. forced air oven for 72 h to evaporate the water to obtain a dry material;
[0065] (4) crushing the dried material into particles with a particle size of 0.1-1 mm;
[0066] (5) The particles obtained in step (4) are heated at 120° C. to carry out an esterification cross-linking reaction for 5 hours to obtain a highly absorbent hydrogel.
[0067] Example 2
[0068] (1) dissolving type I recombinant collagen in water at room temperature to obtain solution I with a mass concentration of 6%;
[0069] (2) adding sodium carboxymethyl cellulose to solution I obtained in step (1), stirring and mixing for 5 hours to obtain solution II, wherein the mass concentration of sodium carboxymethyl cellulose in solution II is 10%;
[0070] (3) Pour solution II from step (2) into a stainless steel plate and dry it in a 60° C. forced air oven for 24 h to evaporate the water to obtain a dry material;
[0071] (4) crushing the dried material into particles with a particle size of 0.05-1 mm;
[0072] (5) The particles obtained in step (4) are heated at 150° C. to carry out an esterification cross-linking reaction for 1 hour to obtain a highly absorbent hydrogel.
[0073] Example 3
[0074] (1) dissolving type III recombinant collagen in water at room temperature to obtain solution I with a mass concentration of 1%;
[0075] (2) adding sodium carboxymethyl cellulose to solution I obtained in step (1), stirring and mixing for 5 hours to obtain solution II, wherein the mass concentration of sodium carboxymethyl cellulose in solution II is 6%;
[0076] (3) Pour solution II from step (2) into a stainless steel plate and dry it in a 40° C. forced air oven for 120 h to evaporate the water to obtain a dry material;
[0077] (4) crushing the dried material into particles with a particle size of 0.2-1.2 mm;
[0078] (5) The particles obtained in step (4) are heated at 100° C. to carry out an esterification cross-linking reaction for 24 hours to obtain a highly absorbent hydrogel.
[0079] Example 4
[0080] (1) dissolving type III recombinant collagen in water at room temperature to obtain solution I with a mass concentration of 3%;
[0081] (2) adding sodium carboxymethyl cellulose to solution I obtained in step (1), stirring and mixing for 5 hours to obtain solution II, wherein the mass concentration of sodium carboxymethyl cellulose in solution II is 8%;
[0082] (3) Pour solution II from step (2) into a stainless steel plate and dry in a blast oven at 50° C. for 48 h to evaporate the water to obtain a dry material;
[0083] (4) crushing the dried material into particles with a particle size of 0.1-1 mm;
[0084] (5) The particles obtained in step (4) are heated at 130° C. to carry out an esterification cross-linking reaction for 8 hours to obtain a highly absorbent hydrogel.
[0085] Example 5
[0086] (1) Dissolve the polypeptide in water at room temperature to obtain a solution I with a mass concentration of 5%;
[0087] (2) adding sodium carboxymethyl cellulose to solution I obtained in step (1), stirring and mixing for 5 hours to obtain solution II, wherein the mass concentration of sodium carboxymethyl cellulose in solution II is 6%;
[0088] (3) Pour solution II from step (2) into a stainless steel plate and dry in a 50° C. forced air oven for 72 h to evaporate the water to obtain a dry material;
[0089] (4) crushing the dried material into particles with a particle size of 0.1-1 mm;
[0090] (5) The particles obtained in step (4) are heated at 120° C. to carry out an esterification cross-linking reaction for 5 hours to obtain a highly absorbent hydrogel.
[0091] Example 6
[0092] (1) Dissolving the oligopeptide in water at room temperature to obtain a solution I with a mass concentration of 5%;
[0093] (2) adding sodium carboxymethyl cellulose to solution I obtained in step (1), stirring and mixing for 5 hours to obtain solution II, wherein the mass concentration of sodium carboxymethyl cellulose in solution II is 6%;
[0094] (3) Pour solution II from step (2) into a stainless steel plate and dry in a 50° C. forced air oven for 72 h to evaporate the water to obtain a dry material;
[0095] (4) crushing the dried material into particles with a particle size of 0.1-1 mm;
[0096] (5) The particles obtained in step (4) are heated at 120° C. to carry out an esterification cross-linking reaction for 5 hours to obtain a highly absorbent hydrogel.
[0097] Comparative Example 1
[0098] (1) at room temperature, dissolving tartaric acid in water to obtain a solution I having a mass concentration of 0.02%;
[0099] (2) adding sodium carboxymethyl cellulose to solution I obtained in step (1), stirring and mixing for 5 hours to obtain solution II, wherein the mass concentration of sodium carboxymethyl cellulose in solution II is 6%;
[0100] (3) Pour solution II from step (2) into a stainless steel plate and dry in a 50° C. forced air oven for 72 h to evaporate the water to obtain a dry material;
[0101] (4) crushing the dried material into particles with a particle size of 0.1-1 mm;
[0102] (5) The particles obtained in step (4) were heated at 120° C. to carry out an esterification cross-linking reaction for 5 h to obtain a hydrogel.
[0103] Comparative Example 2
[0104] Steps (2) to (5) are the same as those in Example 1, except that in step (1), type III recombinant collagen is dissolved in water at room temperature to obtain solution I with a mass concentration of 10%.
[0105] Comparative Example 3
[0106] Steps (1) to (4) are the same as those in Example 1, except that step (5) is to heat the particles obtained in step (4) at 160° C. to carry out an esterification cross-linking reaction, and the reaction time is 36 hours.
[0107] Comparative Example 4
[0108] Steps (1) and (3)-(5) are the same as those in Example 1, except that step (2) is to add sodium carboxymethyl cellulose to solution I obtained in step (1) and stir and mix for 5 hours to obtain solution II, wherein the mass concentration of sodium carboxymethyl cellulose in solution II is 3%.
[0109] Swelling test
[0110] (1) Place a dry sintered glass funnel on a stand and pour 40.0 ± 1.0 g of pure water into the funnel;
[0111] (2) Wait until no droplets are detected in the funnel neck (about 5 minutes) and dry the funnel tip with absorbent paper;
[0112] (3) Place the funnel into a dry, empty glass beaker (Beaker 1), place it on a balanced balance and record the weight of the empty device (W 配平 );
[0113] (4) Place a magnetic stirring bar in a 100 mL beaker (Beaker 2), place Beaker 2 on a balance and balance it;
[0114] (5) Add 40.0±1.0 g SGF / water (mass ratio 1:8) solution into beaker 2;
[0115] (6) Place beaker 2 on a magnetic stirrer and stir slowly at room temperature;
[0116] (7) Use weighing paper to accurately weigh 0.250±0.005 g of the hydrogel powder of Examples 1-6 and Comparative Examples 1-4 (W in );
[0117] (8) Add the above powder to beaker 2 and stir slowly with a magnetic stirrer without creating a vortex for 30±2 minutes;
[0118] (9) Remove the stirring bar from the resulting suspension, place the funnel on a stand and pour the suspension into the funnel, using a spatula to collect any remaining material;
[0119] (10) Excretion of substances, lasting 20 ± 2 minutes;
[0120] (11) Place the funnel containing the discharged material in beaker 1 and weigh it (W ’ fin ).
[0121] The swelling degree was calculated according to the following formula:
[0122] Swelling degree = (W fin -W in ) / W in .
[0123] W fin is the weight of the swollen hydrogel calculated as follows: W fin =W ’ fin –W 配平 ;
[0124] W in is the weight of the initial dry sample.
[0125] The swelling test results of Examples 1-6 and Comparative Examples 1-4 are shown in Table 1.
[0126] Table 1 Swelling test results of Examples 1-6 and Comparative Examples 1-4
[0127] sample Swelling degree Example 1 95.35 Example 2 97.48 Example 3 90.26 Example 4 94.54 Example 5 88.51 Example 6 87.25 Comparative Example 1 64.43 Comparative Example 2 52.14 Comparative Example 3 47.23 Comparative Example 4 55.16
[0128] It can be seen from Table 1 that when recombinant collagen is added as a cross-linking agent (Example 1), the swelling degree is greatly improved compared to tartaric acid (Comparative Example 1). This is because the recombinant collagen provides a longer chain length as a cross-linking agent. In the cross-linked structure, a loose polymer network structure can be formed, which helps to increase the water absorption rate of the hydrogel.
[0129] Compared with Example 1, in Comparative Example 2, the concentration of type III recombinant collagen in water was changed to 10%. Too high a cross-linking agent content would increase the cross-linking density, making the gaps between the polymer networks small, making it difficult for water molecules to penetrate into the interior of the polymer, thereby reducing the swelling degree.
[0130] Compared with Example 1, Comparative Example 3 changed the temperature and time of the esterification cross-linking reaction. Although the content of the cross-linking agent was appropriate, too high a cross-linking temperature would also lead to excessive cross-linking, affecting the penetration of water molecules, thereby reducing the swelling degree;
[0131] Compared with Example 1, Comparative Example 4 changes the mass concentration of sodium carboxymethyl cellulose in Solution II, which leads to a decrease in solid content concentration. In contrast, the content of the crosslinking agent is too high, which will also lead to an increase in the crosslinking density, thereby reducing the swelling degree.
[0132] The present invention uses recombinant collagen and its hydrolyzed oligopeptides or polypeptides as crosslinking agents. The main chain ends and side chains of the crosslinking agent contain abundant carboxyl and amino groups, which can react with the polysaccharide chain in sodium carboxymethyl cellulose to generate a loose polymer network and improve the water absorption rate. On the other hand, the addition of recombinant collagen or polypeptides can also be used as an energy substance to provide energy for the body and prevent malnutrition caused by long-term reduction of food intake. The present invention proposes for the first time to prepare hydrogels by crosslinking recombinant collagen / polypeptides with sodium carboxymethyl cellulose. The preparation method is simple, safe and non-toxic. After consuming the hydrogel of the present invention, there is a sense of fullness and energy can be provided to the body, which broadens the selection of gastrointestinal fillers. For example, the highly absorbent hydrogel of the present invention can be used to prepare drugs for treating overweight or obesity, drugs for treating sleep apnea, or drugs for treating diabetes.
[0133] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a highly absorbent hydrogel, characterized in that: The method is prepared by using recombinant collagen or peptide compounds as crosslinking agents and crosslinking with sodium carboxymethyl cellulose, and comprises the following steps: dissolving a cross-linking agent in water to obtain a solution I; Adding sodium carboxymethyl cellulose to the solution I to obtain a solution II; The solution II is dried and crushed into particles, which are then heated to undergo esterification and cross-linking reaction to obtain the highly absorbent hydrogel.
2. The method for preparing a highly absorbent hydrogel according to claim 1, characterized in that: The mass concentration of the cross-linking agent in the solution I is 1-6%; The mass concentration of sodium carboxymethyl cellulose in the solution II is 6%-10%.
3. The method for preparing a highly absorbent hydrogel according to claim 1, characterized in that: The recombinant collagen is selected from one or more of type I, type II, type III, type V, type IV and type XVII; The peptide compound is selected from one or both of oligopeptides and polypeptides.
4. The method for preparing a highly absorbent hydrogel according to claim 1, characterized in that: The drying temperature is 40-60°C and the drying time is 24-120h; The temperature of the esterification cross-linking reaction is 100-150° C., and the time is 1-24 hours.
5. The method for preparing the highly absorbent hydrogel according to claim 1, characterized in that: The particle size of the particles is 0.05-5 mm.
6. A highly absorbent hydrogel, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 5.
7. Use of the highly absorbent hydrogel according to claim 6 in the preparation of a medicament for treating overweight or obesity.
8. Use of the highly absorbent hydrogel according to claim 6 in the preparation of a medicament for treating sleep apnea.
9. Use of the highly absorbent hydrogel according to claim 6 in the preparation of a medicament for treating diabetes.
Citation Information
Patent Citations
Collagen sponge as well as preparation method and application thereof
CN106075576A
Method for producing hydrogels coupling high elastic modulus and absorbance
CN107250164A
Recombinant collagen gel dressing as well as preparation method and application thereof
CN115770323A
Hydrogels having enhanced elasticity and mechanical strength properties
US20030232895A1